Formulation of grease from industrial waste - Tan, Swee Sing (2014)
Grease is a semisolid lubricant which helps in reducing the friction between two surfaces. Lubricating grease can be applied to mechanical parts which runs intermittently or being stored for a long period or in contact with the moisture that will cause corrosion to happen. The growing demand on lubricating grease has increased the attention on quality of the grease. A better performance and more environmental friendly bio-grease is preferable. Mixture of Spent Bleaching Earth and Waste Cooking Oil are the base grease for the research. To enhance the rheological properties of the grease, three types of cellulose are added to the grease which are Methyl Cellulose (MC), Carboxymethyl Cellulose (CMC) and Hydroxyethyl Cellulose (HEC). Three types of test were carried out to test the consistency, contamination and also the oil bleed of the formulated grease. The test method for consistency of grease is accordance to ISO 2137 and NLGI (National Lubricating Grease Institute) Number was obtained. The result showed that 75% to 80% of SBE and 20% to 25% of WCO were needed to produce grease with NLGI Number 2 and 3. Addition of less than 10% of additive decreased the amount of SBE needed to about 25%. Among three types of cellulose added, Hydroxyethyl Cellulose has the most improvement to the consistency of the formulated grease. While for oil bleeding test, Methyl Cellulose showed the best performance which is about 35% in reducing the oil separation condition